Accuracy of dermoscopic criteria for the differentiation between superficial basal cell carcinoma and Bowen's disease. (15th July 2018) - Papageorgiou, C.; Apalla, Z.; Variaah, G.; Matiaki, F.C.; Sotiriou, E.; Vakirlis, E.; Lazaridou, E.; Ioannides, D.; Lallas, A.
Abstract: Background: The dermoscopic features of superficial basal cell carcinoma (sBCC) and Bowen's disease (BD) have been extensively investigated, and dermoscopy was shown to significantly improve their recognition. However, incorrectly diagnosed cases still exist, with a considerable number of sBCCs dermoscopically interpreted as BD. Our aim was to investigate the dermoscopic variability in sBCC and BD on different anatomic sites, to identify potent dermoscopic predictors for each diagnosis and to investigate the potential source of the inaccurate clinico‐dermoscopic diagnosis of some sBCCs. Methods: Dermoscopic images of histopathologically diagnosed sBCC and BD were evaluated by three independent investigators for the presence of predefined criteria. Subsequently, three independent investigators with expertise in dermoscopy classified the tumours as sBCC or BD based on the dermoscopic image. Diagnostic accuracy scores were calculated and crude and adjusted odds ratios, and 95% confidence intervals were calculated by univariate and conditional multivariate logistic regression, respectively. Results: A total of 283 lesions were included in the study (194 sBCCs and 89 BD). The main dermoscopic predictors of BD were dotted vessels (7.5‐fold) and glomerular vessels (12.7‐fold). The presence of leaf‐like areas/spoke‐wheel areas/concentric structures (OR = 0.027) and arborizing vessels (OR = 0.065) has predicted sBCC. Multivariate risk factors for sBCC misclassification were the location on lower extremities (OR = 5.5), the presence of dotted vessels (OR = 59.5) and the presence of large ulceration (OR = 6.4). In contrast, the presence of brown‐coloured pigmentation was a protective predictor for misdiagnosis (OR = 0.007). Finally, a subgroup analysis of lesions located on lower extremities revealed two additional potent predictors of sBCC: superficial fine telangiectasia (SFT) and whity shiny blotches/strands. Conclusions: Dotted and glomerular vessels are strong predictors of BD. When located on the lower extremities, sBCC may also display dotted vessels, rendering its recognition problematic. On the latter anatomic site, clinicians should consider SFT and whity shiny blotches/strands as additional sBCC predictors.